Walkers with visual-impairments in the British countryside: Picturesque legacies, collective enjoyments and well-being benefits. (April 2017) - Macpherson, Hannah
Abstract: This paper draws on ethnographic research to explore the experiences of members of specialist blind and visually impaired walking groups who visit areas of the Peak District and Lake District, notable rural locations in Britain. For many people, a visit to these areas is associated with the apprehension of picturesque beauty through the physical faculty of sight. However, data from participant observation and interviews reveal that people also derive many other key social, well-being and health benefits by visiting and walking in these areas. This paper identifies some of these other benefits and places them within the context of recent theory that addresses therapeutic landscapes and people with visual-impairments' cultural and sensory apprehensions. The well-being experiences of visually-impaired walking participants are identified and include; exploration outside of known (usually urban) routes; reaching summits and areas that have collective symbolic value; the facilitation of social networks; and improvements in physical fitness and self-reported weight loss or maintenance. The paper combats a pervasive ocularcentrism in appraisals of British landscape and contributes to emerging debates on 'therapeutic mobilities' - a place where disability and rurality intersect.